Om Bent Christensens disputats: Omkring Grundtvigs Vidskab - Thyssen, A. Pontoppidan (Grundtvig-studier, 1999)
About Bent Christensen’s Dissertation for the Doctorate, » About Grundtvig ’s Vidskab « By Anders Pontoppidan Thyssen